Use of T-SPOT.TB in latent tuberculosis infection diagnosis in general and immunosuppressed populations - Piana, Federica; Ruffo Codecasa, Luigi; Baldan, Rossella; Miotto, Paolo; Ferrarese, Maurizio; Cirillo, Daniela Maria (The New microbiologica, 2007)
Immunosuppressed patients have a nine-fold greater risk of developing active tuberculosis (TB) disease given the latent TB infection than the general population. Few data are available on the predictivity of T-SPOT.TB in immunosuppressed patients. We had a T-SPOT.TB determination and a TST from 197 immunosuppressed haematological patients and 324 community contacts of infectious TB cases. In the general population, TST was positive in 275 (84.9%), T-SPOT.TB in 167 (51.5%) (p < 0.0001). In immunosuppressed patients, TST was positive in 34 (17.3%), T-SPOT.TB in 70 (35.5%). T-SPOT.TB is not influenced by immunosuppression and even an indeterminate result may yield useful information on patient's anergy.